2022
DOI: 10.3390/molecules27123958
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Calculating the Relative Permeability Curve of Polymer Flooding Based on the Viscosity Variation Law of Polymer Transporting in Porous Media

Abstract: Relative permeability of polymer flooding plays a very important role in oil field development. This paper aimed to measure and calculate the relative permeability curves of polymer flooding more accurately. First, viscosity variation law of polymer in porous media was studied. Rock particles of different diameters and cementing agent were used to make artificial cores and hydrophobically associating polymer solutions were prepared for experiments. Polymer solutions were injected into the cores filled with cru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…The new k ro is a function of the original relative permeability (k 0 ro ), water saturation (S w ) and polymer concentration (C p ). The new curve for the relative permeability is illustrated in Figure 21, and it tends to reproduce the slight variations in the relative oil permeability reported by several authors [44,50,51].…”
Section: Modified Polymer Floodingsupporting
confidence: 64%
See 1 more Smart Citation
“…The new k ro is a function of the original relative permeability (k 0 ro ), water saturation (S w ) and polymer concentration (C p ). The new curve for the relative permeability is illustrated in Figure 21, and it tends to reproduce the slight variations in the relative oil permeability reported by several authors [44,50,51].…”
Section: Modified Polymer Floodingsupporting
confidence: 64%
“…The parameters in Equation ( 22) are taken from laboratory measurements, and C p is the polymer concentration. The polymer solution viscosity at zero shear rate depends on the polymer concentration and salinity and is defined by the Flory-Huggins equation (Equation (22c)), where A p1 , A p2 , A p1 and S p are input parameters and C sep represents the effective salinity for polymer [44]. The maximum shear-thickening viscosity can be described by Equation (22), where A p11 and A p22 are input parameters.…”
Section: Physical Properties Rheology and Degradationmentioning
confidence: 99%
“…This result shows that the associated polymer exhibited completely different viscoelastic behavior after association than before association, entangling the molecular groups after shear damage, restoring part of the structural characteristics, and maintaining a certain elastic deformation capacity of the system [ 26 ]. This result also shows that, although the polymer solution injected into the formation was subject to shear failure, the elastic deformation of the system still produced greater elastic viscosity at the small pore throat when passing through the porous medium; thus, mobility control and a better oil displacement effect were achieved [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Most of the previous research has focused on the mechanism of recovery enhancement by polymer drives and the development of new polymers. For example, Jiang et al [28] viscosity variation law of polymer in porous media was studied, measured, and calculated the relative permeability curves of polymer flooding more accurately. Lu et al [29] demonstrated the relationship between the concentration and viscosity of polymer displacement agents and the effectiveness of displacement and proposed a method to improve the effectiveness of polymer displacement.…”
Section: Compatibility Determinationmentioning
confidence: 99%